The Utility of Preoperative Phone Calls for Endoscopic Sinus Surgery Procedures. Issue 1 (January 2022) - Dang, Sabina; McKeon, Mallory; Menon, Varun; Chandra, Rakesh; Bennett, Marc L.
Objective: Perioperative patient education improves patient satisfaction, surgical outcomes, and can reduce postoperative call volume. Here, we investigate whether the use of standardized preoperative phone calls elicits similar results in patients undergoing endoscopic sinus surgery (ESS). Methods: Patients undergoing ESS at a tertiary rhinology center were identified prospectively through the electronic medical record (EMR). In the intervention cohort, a standardized preoperative educational phone call was performed. A postoperative survey was utilized to collect self-assessment of satisfaction and understanding in all patients. Postoperative call rates were obtained from the EMR. Wilcoxon rank sum and chi-squared analyses were conducted to compare results. Demographics of the otology and rhinology cohorts were compared with a Mann Whitney U-test. Results: Data from 43 cases and 58 controls were collected. Patients receiving the intervention were similar to controls with regard to patient-reported understanding (case:9.1 ± 1.1 vs control:9.0 ± 1.4, p  = 0.801) and satisfaction (case:9.4 ± 1.1 vs 8.9 ± 1.4, p  = 0.155). Both cases and controls called the clinic regarding surgical outcomes more often than for postoperative medications or administrative concerns. Independent of receiving the intervention, patients that did not call clinic postoperatively had significantly better understanding of their procedures (call:8.6 ± 1.6 vs no-call:9.5 ± 1.0, p  < 0.015) and satisfaction with their experience (call:8.8 ± 1.4 vs no-call:9.5 ± 1.1, p  < 0.028). Patient age may contribute to lack of impact in the rhinology cohort, as compared to the otology group, but socioeconomic status does not seem to differentiate the two samples. Conclusion: Though shown in other settings, a significant impact of educational phone calls prior to surgery was not observed in this sample. Patient education calls prior to endoscopic sinus surgery were not associated with changes in postoperative call volume to the clinic. Patient understanding and satisfaction may be related to other factors, such as patient selection or demographics. Future studies may target such patients prior to ESS.